2019
DOI: 10.20537/nd190314
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for Phase Locking and Dephasing of Autoresonant Pumping

Abstract: We study the asymptotic behavior of nonlinear oscillators under an external driver with slowly changing frequency and amplitude. As a result, we obtain formulas for properties of the amplitude and frequency of the driver when the autoresonant behavior of the nonlinear oscillator is observed. Also, we find the measure of autoresonant asymptotic behaviors for such a driven nonlinear oscillator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Moreover, in the general case, this method is not applicable to systems with decaying perturbations due to the appearance of metastable states (see, for example, [48]). In addition, the asymptotic approximations obtained for similar systems but with a small parameter in front of the perturbations were justified only in weakly nonlinear cases on asymptotically long but finite time intervals [20,26,29]. In the present paper, a small parameter is not introduced and the behavior of solutions at infinity is discussed.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, in the general case, this method is not applicable to systems with decaying perturbations due to the appearance of metastable states (see, for example, [48]). In addition, the asymptotic approximations obtained for similar systems but with a small parameter in front of the perturbations were justified only in weakly nonlinear cases on asymptotically long but finite time intervals [20,26,29]. In the present paper, a small parameter is not introduced and the behavior of solutions at infinity is discussed.…”
mentioning
confidence: 92%
“…Later it was found that the autoresonance has a wide range of applications and can be used in many systems (see, for example, [37,19,18]). Mathematical models associated with the autoresonance have been considered in many papers [17,26,29,32,46], where mainly weakly nonlinear systems were analyzed. In this paper, the presence of a small parameter is not assumed.…”
mentioning
confidence: 99%
See 1 more Smart Citation